Unexplored Nutritional Potential of Oilseed Meals to Combat Malnutrition - Karnika; Asha kawatra (Archives of Current Research International, 2025)
Background: Malnutrition persists as a formidable global health challenge, particularly in developing regions. Oilseed meals, often regarded as agro-industrial byproducts, possess remarkable nutritional potential that remains largely untapped. This study explores the unexplored nutritive value of sesame, groundnut, and flaxseed meals and their role in addressing malnutrition. Aim: The study aimed to assess the nutritional composition, sensory acceptability, and potential contribution of oilseed meal-based products to addressing malnutrition. Methodology: A comprehensive nutritional evaluation was undertaken to analyze the proximate composition and bioactive components present in sesame, groundnut, and flaxseed meals. Functional food products were formulated utilizing these nutrient-dense ingredients and subjected to sensory analysis to determine consumer acceptability. The most well-received products were further assessed for their nutritional profile to validate their functional food status. Results: The analysis revealed that oilseed meals are rich sources of protein, fiber, and fats. Sensory evaluation indicated high acceptability scores for the formulated products, demonstrating their potential for incorporation into diets. Conclusion: Oilseed meals exhibit substantial nutritional benefits and sensory acceptance, making them viable options for combating malnutrition. Their incorporation into daily diets can enhance nutrient intake in vulnerable populations. The study highlights the need for further research and policy interventions to promote the utilization of oilseed meals in food systems.